SERS of the anti‐inflammatory drug piroxicam adsorbed on the surface of silver or gold colloids as nanocarrier model. (20th November 2015) - Hernandez, M.; Corda, E.; Garcia‐Ramos, J. V.; Domingo, C.; Sevilla, P.
Abstract : Piroxicam is a non‐steroidal anti‐inflammatory drug actually used with limitations because of serious side effects. It is poorly soluble in pure water and exhibit a minimum of four conformers according to the pH conditions of the solution, but not all of them are medically active. In this study, we present, firstly, the Raman characterization of piroxicam in different organic solvents (dimethyl sulfoxide, 1, 4‐dioxane, ethanol, 1‐propanol). These results have permitted us to analyze surface‐enhance Raman scattering spectra of piroxicam adsorbed on gold or silver nanoparticles surface at several pHs (1, 2, 4, and 7), imitating the environment of the drug in the body, either in the gastrointestinal tract or in healthy and disease tissues. Results indicate that, below pH = 7, piroxicam is mainly in the zwitterionic conformer, and molecules are oriented parallel to the noble metal surface; however at pH ≥ 7, the main specie detected is the anionic one, differently oriented with respect to the nanoparticle surface. The metal‐piroxicam systems here characterized by surface‐enhance Raman scattering spectroscopy could constitute nanocarriers in future projects of transporting and releasing of the drug in the body. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We present the Raman characterization of piroxicam in different organic solvents, which have permitted us to analyze surface‐enhance Raman scattering spectra of the drug adsorbed on gold or silver nanoparticles surface at several pHs, imitating the environment of the drug in the body. Results indicate that, below pH = 7, the zwitterionic form predominates, however, at higher pHs, it is the anionic one, differently oriented with respect to the nanoparticle surface.